Evaluation of Growth and some Growth Analysis Components in Sugar beet Genotypes Grown under Low Nitrogen Fertilizer Levels in Khartoum State- Sudan - Suleiman A.A.; Z.A.Yousif; M.Idris B.; M. Musa S.; A.Madam Haroun; A. Mubark A.; H. Talib N.; Zienelabiedien N. (Journal of Agronomy Research, 2023)
This investigation was carried out at the Demonstration Farm of the College of Agriculture- University of Bahri during 2018/2019 winter season to evaluate growth (morphological) and growth analysis (physiological) components in some sugar beet (Beta vulgaris L) genotypes under different nitrogen levels to know how well sugar beet plant performs during the growing season, Thus, to provide information to assist producers in identifying and introducing superior genotype and good management of nitrogen application in AlKadro area. The experiment was laid out in split plot design. The genotypes used were namely, Blaladi. Strube Sudan 01/14, Strube Sudan 02/14, Strube Sudan 04/14, Strube Sudan 05/14 and Strube Sudan 06/14, and the nitrogen levels were viz, 0, 80 and 120 kg urea per ha; applied twice (at the sowing and then 4 weeks after sowing). The evaluated components were; leaf number/plant, leaf area index (LAI), root length, root diameter, fresh and dry weight of foliage/plant, fresh and dry weight of root/plant; all determined at 5 terms. While Crop Growth Rates (CGR), Relative Growth Rate (RGR) and Net Assimilation Rate (NAR); determined at different periods of growth (intervals). The analysis of variance (ANOVA) revealed that at 4 weeks after sowing (WAS): leaf number (14.33- 17.03) , root length (19.05 – 21.75 cm), root diameter ( 7.93- 8.40 cm) foliage fresh ( 186.93 – 292.06 g) and dry ( 69.00 – 94.10 g) weight per plant, root fresh (72.66 – 108.88 g) and dry weight ( 12.54 – 22.08 g) per plant differed significantly (P≤ 0.05); at 7 and 10 WAS leaf number (22.39 -35.73 and 26.91 – 38.47, respectively), LAI ( 3.725 -5.645) , fresh and dry root weight per plant ( 586.78 – 913.81an 189.06 – 326.43 g, respectively) differed significantly; at 13 WAS: dry foliage weight ( 69.00 – 94.10 g), LAI ( 2.603 – 4.744), root diameter (10.09 – 11.92 cm) differed significantly; at 16 WAS only dry foliage (44.34 – 73.48 g) weight reflected significance. All other cases reflected insignificant differences among the evaluated genotypes. Moreover, all the studied components reflected insignificant differences among the nitrogen fertilizer levels and likewise genotype x nitrogen interaction (G x N) at the 5 sampled terms. Nevertheless, CGR, RGR and NAR displayed insignificant effect on the studied components in the evaluated periods.
Keywords: Crop Growth Rate